2020
DOI: 10.1016/j.cortex.2020.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical and cognitive correlates of domain-specific anosognosia in early Alzheimer's disease

Abstract: This is a repository copy of Neuroanatomical and cognitive correlates of domain-specific anosognosia in early Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 77 publications
(95 reference statements)
5
14
0
Order By: Relevance
“…A comprehensive overview of the results in the present study indicates that the anterior cingulate cortex has a strong involvement in the overall clinical manifestation of multi-domain anosognosia. Structural changes are commonly seen later than functional changes in the course of AD (Ewers et al, 2011), but there is, however, evidence that variability in gray matter of the anterior cingulate cortex is related to non-memory and total anosognosia in early AD (Valera-Bermejo et al, 2020). The present rs-fMRI findings extend the involvement of this structure to anosognosia for multiple cognitive domains.…”
Section: Functional Connectivity Associated With Total Anosognosiasupporting
confidence: 45%
See 2 more Smart Citations
“…A comprehensive overview of the results in the present study indicates that the anterior cingulate cortex has a strong involvement in the overall clinical manifestation of multi-domain anosognosia. Structural changes are commonly seen later than functional changes in the course of AD (Ewers et al, 2011), but there is, however, evidence that variability in gray matter of the anterior cingulate cortex is related to non-memory and total anosognosia in early AD (Valera-Bermejo et al, 2020). The present rs-fMRI findings extend the involvement of this structure to anosognosia for multiple cognitive domains.…”
Section: Functional Connectivity Associated With Total Anosognosiasupporting
confidence: 45%
“…Two recurring regions from our pattern of findings were the fusiform and lingual gyri. These structures have also been associated with anosognosia and reduced brain gray matter volumes in early AD (Guerrier et al, 2018;Valera-Bermejo et al, 2020). Functional alterations of the fusiform (Vannini et al, 2017) and lingual gyrus (Mitelpunkt et al, 2020) have been found to be associated with anosognosia in AD and might have strong links with regions within a broader network in charge of sustaining cognitive awareness.…”
Section: Functional Connectivity Associated With Memory Anosognosiamentioning
confidence: 98%
See 1 more Smart Citation
“…In summary, reviewing the results of this paper, the ECN involved in frontal and parietal regions showed a downward trend in MCI patients. Areas of the ECN that showed an upward trend are mainly in the occipital, temporal, and subcortical regions with a small portion also rising in the frontal and parietal regions, which may be the compensatory mechanism of the disruption of frontal and parietal lobes in MCI patients (Valera-Bermejo et al, 2020). It is also well-established that the frontal and parietal regions are crucial aspects of the ECN, which send rich sensory information not only for movement controls, but also for other cognitive abilities, especially in executive function (Roh et al, 2020).…”
Section: Special Imaging Abnormal Markersmentioning
confidence: 95%
“…Similarly, Sapey-Triomphe et al (2015) showed positive associations between volumes of the left ACC and right OFC and proxies of affective processing measured through an emotion recognition task. In early-AD, alterations in the left ACC underpin deterioration in self-awareness ( Amanzio et al, 2011 ; Valera-Bermejo et al, 2020 ), and sustain the creation of complex self-other brain representations ( Amodio and Frith, 2006 ). In addition to the ACC, affective ToM was also associated with the left OFC.…”
Section: Discussionmentioning
confidence: 99%